Growth rates and specific motor abilities as a function to predict the selection of talents taekwondo sport (Egyptian national project) - Mohammed Mustafa Bakr (Turkish Journal of Kinesiology, 2016)
The aim of this study is to investigate the contribution ratios of Growth rates and specific motor abilities as a function to predict the selection of talented taekwondo sport. The study was carried out on a sample of (755) individual Clubs and youth centers across the governorates of Egypt, and the average age (11.64 ± 0.48 years), height (144.06 ± 7.04 cm) and weight (36.86 ± 7.51 kg). Tests were conducted in the period from 7/11/2011 to 29/12/2011 selected individuals underwent the following tests and measurements (Ability, Hinge flexibility basin, Agility, Kinetics speed in level trunk, Kinetics speed in level face, Endure Performance, Performance ), the researcher used the descriptive survey method. The statistical analysis SPSS was used to apply formulas statistical by calculating: average, standard deviation, correlation, stepwise regression. The results showed that the growth rates and special motor abilities contribute to the selection of talented taekwondo. In addition, taekwondo players are characterized by flexibility, Endure performance and motor speed. The study concluded that there are five factors affect the selection of talented junior Taekwondo detailed flexibility contribute (28.8%), endure Performance contribute by (15.1%), ability contribute (7.8%), Growth rates (age, length, weight) a contribution rate (5.2%), kinesthetic speed motor (in the level of the trunk - in the face level) (1.1%). Predictable talented selection junior taekwondo through the following equation = 49.835 + Age (-0.389) + Length (0.157) + Weight (-0.188) + Flexibility (-0.359) + Ability (0.081) + Agility (-2.261) + Endure Performance (0.608) + Kinetics speed motor in the level of the trunk (0.586) + Kinetics speed motor in the face level (0.260). These results should be taken into account by the taekwondo Federation and trainers for use as an indicator for selecting talented taekwondo sport.